Screening for Thalassemia in Healthy Population at a Tertiary Care Hospital in Eastern Nepal - Das, Manish Kumar; Nepal, Niraj; Chaudhary, Prabesh (Journal of Nobel Medical College, 2020)
Background: Thalassemia is a type of congenital anemia, where there is deficient synthesis of one or more type of globin subunits of normal hemoglobin. This study was undertaken with aims & objective to study the prevalence of thalassemia by comparing Red Blood Cell indices, Peripheral Blood Smear and Electrophoresis in adult volunteers. Material and Methods: The study comprised of 518 cases attending hematological department, who were enrolled in our study after proper informed consent, of which 462 cases were further studied. All cases were subjected to blood sampling for estimation of Hemoglobin, red cell indices and peripheral blood smear. Those samples where peripheral blood smear and Red cell indices were suggestive of thalassemia were subjected to Bio-Rad High Performance Liquid Chromatography based electrophoresis to observe the presence of any abnormal hemoglobin. Results: The mean age of screening sample was 42.91 ± 16.85 years with minimum age of 18 years and maximum age of 85 years. The highest number of cases was in between 21-30 years age groups (19.5%) followed by 41-50 years (17.7%). In the study group, 299 (64.7%) cases were male and 163 (35.3%) cases were female. The prevalence of anemia was found to be 48.16% in males and 68.71% in females with overall prevalence of 55.41%. On electrophoresis reports, 19 cases were diagnosed with thalassemia. The only thalassemia observed was thalassemia minor. The prevalence of thalassemia was found to be 4.11%. Conclusion: Significantly high prevalence of thalassemia minor is found in healthy population.